Evaluation of Tuberculosis Disease Surveillance System in DKI Jakarta Province in 2024: Structure, Function and Attribute Analysis - Ferdian Akhmad Ferizqo; Tri Yunis Miko Wahyono; Inggariwati (POLTEKKES KEMENKES PONTIANAK, 2024)
Indonesia ranks second worldwide in tuberculosis cases. Surveillance components for tuberculosis reporting have been facilitated by SITB. Program improvement recommendations should be implemented by smaller units, such as Public Health Centers, by analyzing data and disseminating it to relevant parties, with recommendations also made at the provincial level. This evaluation aims to describe the implementation of tuberculosis surveillance in DKI Jakarta. This descriptive study uses a mixed-methods approach of observation and structured interviews conducted in DKI Jakarta from April to June 2024. Data were sourced from SITB tuberculosis reports and in-depth interviews with nine tuberculosis officers from the Health Sub-Office, Public Health Centers, and hospitals. Surveillance system evaluation covered system structure, core functions, support functions, and system attributes based on WHO guidelines. System structure aspects related to legal aspects, networks, and partnerships are functioning well, although hospitals lack specific implementers. Core functions like detection, data collection, reporting, dissemination, and feedback operate optimally, though analysis and result interpretation are suboptimal. Support functions involving training and resources also need improvement. System attributes such as simplicity, completeness, representativeness, acceptability, and usefulness are optimal, but timeliness remains a challenge. Recommendations include increasing human resource capacity, reporting accuracy, and coverage of preventive therapy.